Diversidade de fungos micorrízicos arbusculares em pomar orgânico no semiárido cearense - Belchior Luiz Dantas (Ciência Rural, 2015)
The arbuscular mycorrhizal fungi (AMF) are key-organisms for maintenance of plant biodiversity in agroecosystems. There is an increasing interest in changes of the microbiological properties in the rhizosphere by its practical and environmental relevance. This research aimed to evaluate the occurrence of AMF in the establishment of fruits under organic management, and to compare them with an area of ​​native vegetation in semiarid Ceará. Soil samples were collected from 0-10cm layer in June, September and December 2010 in different areas. Number of spores, and diversity of AMF were quantified. The dominance of Glomus spores was confirmed in all the areas